2006
DOI: 10.1002/ijc.21900
|View full text |Cite
|
Sign up to set email alerts
|

N7‐methyldeoxyguanosine levels in DNA isolated from cervical cytology samples are associated with smoking

Abstract: Smoking has been associated, in epidemiological studies, with an increased risk of cervical neoplasia. This may be in part due to the presence of tobacco-specific nitrosamines in cervical mucous of smokers, which may result in carcinogenic DNA damage. We have thus examined whether cervical DNA contains alkylation damage arising from exposure to methylating agents (N7-methyldeoxyguanosine, N7-MedG). DNA was extracted from cervical cytology samples and N7-MedG levels were measured using an immunoslotblot assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
6
1
Order By: Relevance
“…Similar to the data from animal studies, the presence of N 7-Me-Gua and other N 7-guanine adducts has been demonstrated ubiquitously in DNA from humans not known to be exposed to alkylating agents (Table 3) [146, 187-196]. Most of these reports investigated DNA from blood samples; either white blood cells (WBC) or individual blood cell types, and measured N 7-Me-Gua by 32 P-postlabeling or HPLC-ECD.…”
Section: Formation Of N7-guanine Adducts In Human Specimensmentioning
confidence: 52%
See 1 more Smart Citation
“…Similar to the data from animal studies, the presence of N 7-Me-Gua and other N 7-guanine adducts has been demonstrated ubiquitously in DNA from humans not known to be exposed to alkylating agents (Table 3) [146, 187-196]. Most of these reports investigated DNA from blood samples; either white blood cells (WBC) or individual blood cell types, and measured N 7-Me-Gua by 32 P-postlabeling or HPLC-ECD.…”
Section: Formation Of N7-guanine Adducts In Human Specimensmentioning
confidence: 52%
“…, formed from potential environmental sources due to their indistinguishable chemical identity. Interestingly, N 7-Me-Gua amounts were 3-fold and 5-fold higher in tumor tissue compared to normal tissues from cervical or bladder tissues, respectively [187, 194]. In contrast, N7-Me-Gua amounts were lower in colon tumor DNA compared to normal colon tissue [192].…”
Section: Formation Of N7-guanine Adducts In Human Specimensmentioning
confidence: 99%
“…The immunoslot blot (ISB) assay was first developed by Nehls and coworkers in 1984 (1). Since then the assay has been applied to the detection of several DNA adducts formed both in vitro (2)(3)(4)(5) and in vivo (6)(7)(8)(9)(10)(11)(12) and the use of both monoclonal (13,14) and polyclonal (2) antibodies has been described.…”
Section: Introductionmentioning
confidence: 99%
“…5 Upon metabolic activation TSNA can form DNA adducts of which N 7 -methylguanine (m 7 Gua) is by far the most abundant, representing 70-90% of methylation products. [6][7][8][9][10] Whereas m 7 Gua is innocuous in DNA, the levels increase dose-dependently in DNA upon administration of methylating agents, correlating with pro-mutagenic and carcinogenic methyl-adducts, such as O 6 -methylguanine and methyladenine, [11][12][13] and may thus serve as biomarker of exposure to methylating agents. Indeed, a physiologically based pharmacokinetic model for interspecies dose extrapolation of dimethyl sulphate has been based on m 7 Gua adducts in the nasal cavity.…”
mentioning
confidence: 99%